Adult dural arteriovenous fistulas in Galen region: More to be rediscovered - Tu, Tianqi; Song, Zihao; Ma, Yongjie; Yang, Chengbin; Su, Xin; He, Chuan; Li, Guilin; Hong, Tao; Sun, Liyong; Hu, Peng; Zhang, Peng; Ye, Ming; et al. (Frontiers in Neurology, 2022)
Background Dural arteriovenous fistulas in Galen region are the most deeply located and most complex type of dural arteriovenous fistulas. However, cases about DAVFs in this region haven’t been well described. Thus, we aimed to summarize the characteristics of galenic DAVFs involving clinical symptoms, anatomical architectures and drainage patterns, providing experientially therapeutic strategies for these lesions precisely based on our 20 years’ clinical experience. Methods We retrospectively examined 31 patients with Galenic DAVFs between January 2000 and June 2021. Comprehensive analysis was carried out based on symptoms, imaging features, feeding arteries, draining veins, number and location of the fistulas, choice of treatment methods and prognosis assessment. Results Twentynine patients received endovascular embolization, and no perioperative deaths occurred. Transarterial approaches were performed in 27 patients, and combined transarterial and transvenous approach in one. And in one case, the access was established by surgical drilling and embolization was done via venous route. Twentyfour cases obtained complete obliteration after first embolization, and another 5 cases received second period-treatment. Only one patient developed cognitive dysfunction after embolization, and the outcome of the remaining patients were improved at long-term follow-up. Conclusion The understanding of symptoms of non-hemorrhagic neurological deficits in DAVF needs to be further clarified. Lesions with pial feeders may be considered firstly when determining surgical orders. Multi-approaches and multistages embolization would be safe and effective. Excessive embolization and deep vein system obstruction should be avoided. Approach creation by surgery would be an innovative way for interventional therapy.